If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + 3 + -4 + 3 = 0 Reorder the terms: 3 + -4 + 3 + 2p = 0 Combine like terms: 3 + -4 = -1 -1 + 3 + 2p = 0 Combine like terms: -1 + 3 = 2 2 + 2p = 0 Solving 2 + 2p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2p = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 2p = 0 + -2 2p = 0 + -2 Combine like terms: 0 + -2 = -2 2p = -2 Divide each side by '2'. p = -1 Simplifying p = -1
| 3d^2-17=0 | | 2p+3-4+12=3 | | Y=2*2+-3 | | -7/4y=35 | | 17=5 | | -10x(x+5)+76=-12-12 | | 2p+3-4+5= | | 10x^(1/3) | | 2p+3-4+2= | | 10x^1/3 | | -3=-5(4x+2)+21x | | 2p+3-4+1= | | 2p+3-4+10= | | 9f-1=4(2f-1)-4(-5+f) | | 2p+3-4+6= | | -4a+16+6a=7a-9a | | 2p+3-4+11= | | -3/4x-5=10 | | -6x-1=-73 | | 1/4x+3=x | | 9-2x+14=13 | | 2p+3-4+12= | | X+3.48=6.14 | | -19-(-45)=x/2 | | -5(b+8)=-7(b+2) | | 0.3x-0.7x-19=1 | | 2.6=-0.2t | | m+12=26 | | 2(4c-1)-6=5c+4 | | 6-3(r+2)=5(r+3)+1 | | -1-1-1-1-1-1-1+6+1=23332 | | 5t-10=i+2 |